Menata Profesi Guru: Membentuk Guru Profesional Berkarakter di Era Globalisasi - Nuraisah, Siti; Yuniati, Suci; Rahmi, Depriwana; Kurniati, Annisah (FKIP Unirow Tuban, 2024)
In the era of globalization, the key role of the teaching profession is to shape the character of the next generation. This research highlights the importance of structuring the teaching profession to build strong and ethical character. Professional teachers must be responsive to global challenges to provide quality education. The implementation of character-driven teaching is reflected in their daily use of competencies, including in pedagogical, social, professional, and personal domains. The aim of this research is to discuss strategies for enhancing the professionalism and character of teachers. The method used is literature review with a qualitative approach. The primary strategy for building professional teachers with character in the era of globalization is through education. Education is not just about transferring knowledge, but also shaping attitudes, values, and positive behaviors in students. Teachers' teaching activities, from planning to evaluation, reflect professionalism in applying various competencies. Thus, this research emphasizes that efforts to build quality character in the era of globalization are not only about changing the learning paradigm but also represent a long-term investment for a sustainable and comprehensive future.